Cover Picture: Bisamidate Prodrugs of 2‐Substituted 9‐[2‐(Phosphonomethoxy)ethyl]adenine (PMEA, adefovir) as Selective Inhibitors of Adenylate Cyclase Toxin from Bordetella pertussis (ChemMedChem 8/2015). Issue 8 (August 2015) - Česnek, Michal; Jansa, Petr; Šmídková, Markéta; Mertlíková‐Kaiserová, Helena; Dračínský, Martin; Brust, Tarsis F.; Pávek, Petr; Trejtnar, František; Watts, Val J.; Janeba, Zlatko
<x xml:space="preserve">Abstract</x> The front cover picture shows the molecular mechanism of inhibition of adenylate cyclase (AC) toxin (ACT) from Bordetella pertussis, the pathogen that causes whooping cough. Upon activation by endogenous calmodulin (CaM), ACT converts ATP into cAMP causing intracellular cAMP concentrations to increase to supraphysiologic levels in an unregulated manner and disruption of the host cell functions. Novel C‐2‐modified analogues of 9‐[2‐(phosphonomethoxy)ethyl]adenine (PMEA, adefovir) in the form of their bisamidate prodrugs were designed and found to be efficient ACT inhibitors. The compounds displayed favorable plasma stability, the ability to be effectively distributed to target tissues, as well as good selectivity for ACT over human AC isoforms AC1, AC2 and AC5. Thus, ACT inhibition with acyclic nucleoside phosphonates may represent a viable strategy to treat whooping cough. For further details, see the Full Paper by M. Šmídková, Z. Janeba, et al. on p. 1351 ff.